Pathophysiological Role of Sodium in Acute Kidney Injury and Chronic Kidney Disease: A Narrative Review - Gozhenko, Anatoliy; Zukow, Walery; Gozhenko, Olena; Ivanov, Dmytro; Vitiukov, Oleksandr (Journal of Education, Health and Sport, 2025)
Background: Sodium homeostasis disruption is a fundamental pathophysiological mechanism in kidney diseases that critically affects the progression of renal dysfunction and the development of cardiovascular complications. Current research demonstrates that sodium plays fundamentally different roles in acute kidney injury (AKI) compared to chronic kidney disease (CKD), necessitating a rethinking of traditional approaches to diagnosis and treatment. Revolutionary discoveries in the field of tissue sodium accumulation, its interaction with glycosaminoglycans, and activation of immune cascades open new horizons for understanding the pathogenesis of kidney diseases and developing personalized therapeutic strategies. Of particular importance is the analysis of the pathophysiological impact of sodium on vascular regulation, immune response, and kidney function in the context of chronic diseases, which allows revealing complex mechanisms of interaction between electrolyte imbalance and systemic pathological processes. Study Objective: To conduct a comprehensive narrative review of the pathophysiological role of sodium in acute kidney injury compared to chronic kidney disease, systematically analyze molecular mechanisms of action, cellular effects, epigenetic modifications, and clinical strategies for sodium management with special emphasis on pediatric aspects and age-related features. The aim of this work is to analyze the pathophysiological impact of sodium on vascular regulation, immune response, and kidney function in the context of chronic diseases. The study includes evaluation of the latest advances in understanding tissue sodium accumulation, its immunomodulatory properties, interaction with the microbiome, and the potential of personalized medicine for optimizing therapeutic approaches in modern nephrological practice considering genetic polymorphisms, biomarkers, and age-specific characteristics of patients. Methods: A systematic literature search was conducted in international databases PubMed, Scopus, Web of Science, Cochrane Library, EMBASE, and specialized Ukrainian scientific resources for the period 2010-2025 using specific search terms, MeSH headings, and Boolean operators. The primary search identified 1,847 publications, from which 85 high-quality studies were selected for detailed analysis after applying strict inclusion and exclusion criteria and quality assessment using Newcastle-Ottawa and Cochrane Risk of Bias 2.0 scales. Key publications for critical analysis: 47 publications. These studies represent data from 127,543 participants from 34 countries worldwide, including randomized controlled trials, prospective cohort studies, systematic reviews, and meta-analyses. Main Results: Sodium demonstrates fundamentally different pathophysiological roles in AKI compared to CKD at molecular, cellular, and systemic levels. In AKI, sodium dysregulation manifests through acute hemodynamic changes with rapid decline in glomerular filtration rate by 25-50% within 24-48 hours, immediate activation of neurohumoral systems with renin levels increasing over 200% and norepinephrine over 150%, development of critical electrolyte imbalance, and activation of cellular stress pathways. In CKD, sodium accumulates in tissues through complex mechanisms of interaction with glycosaminoglycans of the interstitial matrix, leading to formation of osmotically active sodium depots that can exceed normal values by 150% in patients with stage 5 CKD. This tissue accumulation activates the transcription factor TonEBP/NFAT5, which induces persistent inflammation with increases in interleukin-6 levels by 189% and tumor necrosis factor-α by 156%, demonstrating the critical impact of sodium on vascular regulation and immune response in chronic diseases. Clinical Conclusions: Meta-analysis shows that high sodium consumption (>6 g/day) in CKD patients increases cardiovascular event risk by 23% (relative risk 1.23, 95% confidence interval: 1.11-1.36), overall mortality by 18% (relative risk 1.18, 95% confidence interval: 1.07-1.31), and heart failure hospitalizations by 34% (relative risk 1.34, 95% confidence interval: 1.19-1.51). A U-shaped relationship between sodium consumption and treatment outcomes was revealed with optimal consumption of 4-6 g/day. Conclusions: Optimization of personalized sodium management strategies adapted to the pathophysiological features of AKI and CKD with consideration of age-related characteristics has significant potential for improving renal and cardiovascular outcomes. Evidence-based recommendations for stage-specific sodium management were developed and promising directions for future research in personalized nephrology were identified.